An Overview of Labor Welfare Measures in India in Response to Globalization. Issue 1 (March 2015) - Bhattacharjee, Sharmistha
Globalization refers to complex economic networks of international competition, resource suppliers, and product markets. Most organizations achieve high performance within a complex and competitive global environment. Hence we can see it as a trend in which the economic, political, and cultural activities of people in different countries increasingly influence each other and become interdependent. With the change in the global labor market as a result of globalization, welfare measures are considered as a necessary investment that may save money in the long run and provide employers with a stable labor force. Labor welfare is part of social welfare both conceptually and operationally. It encompasses the state of well-being, happiness, satisfaction, conservation, and development of human resources. This article provides an overview of labor welfare in India.